Pengaruh G-CSF terhadap ANC recoverypada pasien kanker dengan neutropenia - Ningsih, Diana Rachma; Murwanti, Retno; Nugroho, Agung Endro (MEDIA ILMU KESEHATAN, 2023)
Background: Neutropenia can increase morbidity in cancer patients because it can cause an increased risk of infection, delay or discontinue chemotherapy, and decrease the dose of cytotoxic agents which affect the patient's response and clinical outcome. The administration of G-CSF can increase ANC levels in neutropenic patients. The effectiveness of G-CSF was assessed by increasing ANC levels compared to before the administration of G-CSF.Objective: This study aims to determine the effect of G-CSF administration on ANC levels in cancer patients with neutropeniaMethods: This research was conducted at Dr. Kariadi General Hospital Semarang in October-December 2022 period with retrospective cohort method. The sample was cancer patients who experienced neutropenia and were given G-CSF.Results: Administration of G-CSF significantly increased ANC values (p-value 0.00 <0.05), increased by 921.07 ± 647.20 in the administration of filgrastim and 933.13 ± 558.89 in the administration of lenograstim and shortened the duration of ANC recovery (p-value 0.00 <0.05), recovery was 1.5 days shorter with filgrastim and 1.9 days with lenograstim.Conclusion: G-CSF Filgrastim and Lenograstim administration can increase ANC levels and shorten the duration of neutropenia treatment